2020
DOI: 10.1155/2020/9260564
|View full text |Cite
|
Sign up to set email alerts
|

Asystole during Suspension Laryngoscopy: Case Report, Literature Review, and Prophylactic Strategies

Abstract: Transoral laryngeal procedures are considered minimally invasive but may trigger important complications such as severe bradycardia and even asystole mediated by vagal reflex. The literature on this subject is rare. This article aims to review the literature, explain associated mechanisms, establish prophylactic strategies, and highlight the importance of intraoperative safety protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In most patients, these hemodynamic responses are transient; however, in patients with cardiovascular and/or cerebrovascular diseases, these responses might produce dangerous complications ( 25 ). Patients undergoing suspension laryngoscopic surgery encounter the same cardiac reaction secondary to the sympathetic reflex and release of catecholamines, even though the stimulation is much more intensive and is sustained much longer than the transient process of endotracheal intubation ( 26 , 27 ). Paltura et al demonstrated that aerosolized lidocaine could inhibit the sympathetic reflex and block the SLN to effectively improve hemodynamics ( 27 ), and the effects of SLNB were proven in our study again.…”
Section: Discussionmentioning
confidence: 99%
“…In most patients, these hemodynamic responses are transient; however, in patients with cardiovascular and/or cerebrovascular diseases, these responses might produce dangerous complications ( 25 ). Patients undergoing suspension laryngoscopic surgery encounter the same cardiac reaction secondary to the sympathetic reflex and release of catecholamines, even though the stimulation is much more intensive and is sustained much longer than the transient process of endotracheal intubation ( 26 , 27 ). Paltura et al demonstrated that aerosolized lidocaine could inhibit the sympathetic reflex and block the SLN to effectively improve hemodynamics ( 27 ), and the effects of SLNB were proven in our study again.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, bradycardia or asystole could be caused by an increase in vagal response through the parasympathetic nerve fibers from the vagus nerve to the sinoatrial node. Thus, even in the absence of the previously mentioned opioid dose problems, several other conditions could increase vagal tone, that is, induce vagal stimulation and reflex upon laryngeal manipulation, resulting in severe reflexive bradycardia and asystole [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…One suspected mechanism is the direct stimulation of the vagus nerve, also known as the laryngo-cardiac reflex [8]. It is often triggered in suspension laryngoscopy when the blade tip lifts the supraglottic area or laryngeal surface of the epiglottis [5,6]. Following stimulation through mechanical irritation to areas innervated by an internal branch of the superior laryngeal nerve, a sensory branch of the vagus nerve, the afferent signal through the vagus nerve is received by the solitary nucleus of the medulla, and the resulting efferent parasympathetic signal through the vagus nerve leads to bradycardia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in our patient's case, the vital signs may immediately recover without any problems; however, there are reports of cases in which cardiopulmonary resuscitation was needed. [14,15] Therefore, anesthesiologists should be aware of the possibility of induction of the laryngocardiac reflex during intubation.…”
Section: Discussionmentioning
confidence: 99%